2015
DOI: 10.1016/j.expneurol.2015.02.032
|View full text |Cite
|
Sign up to set email alerts
|

A balanced view of choroid plexus structure and function: Focus on adult humans

Abstract: Recently tremendous progress has been made in studying choroid plexus (CP) physiology and pathophysiology; and correcting several misconceptions about the CP. Specifically, the details of how CP, a locus of the blood-CSF barrier (BCSFB), secretes and purifies CSF, generates intracranial pressure (ICP), maintains CSF ion homeostasis, and provides micronutrients, proteins and hormones for neuronal and glial development, maintenance and function, are being understood on a molecular level. Unequivocal evidence tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
181
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(187 citation statements)
references
References 93 publications
(158 reference statements)
6
181
0
Order By: Relevance
“…Contributing to this rhythm, respiration adds to pulsatility, but at a lower frequency [54]. Spector et al [166] suggest that during anaesthesia, with slower and shallower breathing, this mixing effect would be reduced.…”
Section: Pulsatile Flow Of Csfmentioning
confidence: 99%
See 2 more Smart Citations
“…Contributing to this rhythm, respiration adds to pulsatility, but at a lower frequency [54]. Spector et al [166] suggest that during anaesthesia, with slower and shallower breathing, this mixing effect would be reduced.…”
Section: Pulsatile Flow Of Csfmentioning
confidence: 99%
“…Overall, the net CSF flow in adults is through the ventricles to the basal subarachnoid spaces [12,166].…”
Section: Pulsatile Flow Of Csfmentioning
confidence: 99%
See 1 more Smart Citation
“…While studies involving the CSF have identified many potential ALS biomarkers, mass transfer occurs between the blood and CSF at the blood-CSF barrier, predominantly in the subarachnoid space and the choroid plexus [130,131], suggesting that the same biomarkers could be present in both fluid types. This was previously demonstrated where several studies have indicated significantly high correlations between blood (serum and plasma) and CSF levels of the same biomarker [34,38,44,118].…”
Section: Biomarkers In Blood (Serum and Plasma)mentioning
confidence: 99%
“…28,29 The fenestrated capillaries of the choroid plexus are leaky and, in contrast to cerebral endothelia, readily allow the passage of ions and other small molecules. 5,121,124,146 The choroid plexus was first suggested as a site of CSF secretion by Faivre in 1854 41 and by Cushing in 1914, 25 and in 1960, De Rougemont et al 33 provided the first direct experimental evidence of choroid plexus-dependent CSF secretion. Although the theory is controversial, according to most models, the choroid plexus epithelium (CPE) generates a significant fraction, if not the majority, of CSF.…”
Section: Mechanisms Of Csf Secretionmentioning
confidence: 99%